1998
DOI: 10.1152/ajpregu.1998.274.1.r30
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis-induced increase in muscle proteolysis is blocked by specific proteasome inhibitors

Abstract: Recent studies suggest that sepsis stimulates ubiquitin-dependent protein breakdown in skeletal muscle. The 20S proteasome is the catalytic core of the ubiquitin-dependent proteolytic pathway. We tested the effects in vitro of the proteasome inhibitors N-acetyl-l-leucinyl-l-leucinal-l-norleucinal (LLnL) and lactacystin on protein breakdown in incubated muscles from septic rats. LLnL resulted in a dose- and time-dependent inhibition of protein breakdown in muscles from septic rats. Lactacystin blocked both tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
53
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 30 publications
7
53
0
Order By: Relevance
“…Glycolysis is favored over oxidative phosphorylation despite adequate oxygen availability ("aerobic glycolysis", sometimes called the Warburg Effect) [206][207][208]. There is accelerated catabolism of skeletal muscle and perhaps smooth muscle as well [209]. In addition, micronutrient (e.g., vitamins, trace metals) effects are also impaired, reflecting either deficiency or altered activity [210,211].…”
Section: Basic/translational Science What Mechanisms Underlie Sepsis-mentioning
confidence: 99%
“…Glycolysis is favored over oxidative phosphorylation despite adequate oxygen availability ("aerobic glycolysis", sometimes called the Warburg Effect) [206][207][208]. There is accelerated catabolism of skeletal muscle and perhaps smooth muscle as well [209]. In addition, micronutrient (e.g., vitamins, trace metals) effects are also impaired, reflecting either deficiency or altered activity [210,211].…”
Section: Basic/translational Science What Mechanisms Underlie Sepsis-mentioning
confidence: 99%
“…The process was shown to affect total and myofibrillar protein levels and to be associated with elevated ubiquitin mRNA. Subsequent work has established that the response is greater in fastthan in slow-twitch muscle (705) and that sepsis-stimulated proteolysis can be blocked using proteasome inhibitors, both in isolated muscle preparations (315) and intact animals (200) (FIGURE 11E).…”
Section: A the Ubiquitin-proteasome Pathway In Critical Illnessmentioning
confidence: 99%
“…Further, this critical adaptive process of skeletal muscle might facilitate an attenuation in the indirect markers of EIMD following protein consumption (Saunders, 2007). Willoughby et al, (2003) reported an up-regulation of the ubiquitin-proteolytic pathway 48 h following an eccentric exercise bout; indicative of conditions that result in a reduced myofibrillar protein content (Hobler et al, 1998). Hence, efforts to alter protein metabolism and support myofibrillar protein synthesis as soon as possible following EIMD might facilitate recovery.…”
Section: Introductionmentioning
confidence: 99%